A Polyaromatic Molecular Clip That Enables the Binding of Planar, Tubular, and Dendritic Compounds. (22nd February 2017) - Jono, Keisuke; Suzuki, Akira; Akita, Munetaka; Albrecht, Ken; Yamamoto, Kimihisa; Yoshizawa, Michito
Abstract: By the covalent linkage of two bent bisanthracene amphiphiles with a biphenyl spacer bearing hydrophilic pendants, we synthesized a new molecular clip with a C‐shaped conformation. The molecular clip provides an acyclic, open cavity surrounded by four anthracene panels in water. In contrast to previous clip‐ and tweezers‐like compounds as well as cage‐shaped compounds, the C‐shaped polyaromatic cavity displays unusual wide‐ranging capturing abilities toward not only planar perylene‐based pigments and cylindrical single‐walled carbon nanotubes but also highly branched macromolecules (carbazole dendrimers). Abstract : Gäste aller Art willkommen : Eine molekulare Klammer mit C‐förmiger Konformation wurde durch die kovalente Verknüpfung zweier gebogener Bisanthracen‐Amphiphile mit einem funktionalisierten Biphenyl‐Abstandhalter in Wasser hergestellt (siehe Struktur). Die acyclische Kavität der molekularen Klammer erfasst nicht nur planare Pigmente und zylindrische Kohlenstoffnanoröhren, sondern auch hoch verzweigte Makromoleküle (Dendrimere).